What Content Marketing Values Shape Consumers’ Brand Equity? Case of Indonesian Service MSEs - Kolibu, Relinton Jeremia; Silaban, Daniel Peterson; Tindi, Ricardo Gianluigi (Journal of Innovation in Management, Accounting and Business, 2025)
Competition and business sustainability issues are still regarded as the most important challenges for service-based MSEs in Indonesia. Most Indonesian MSEs can only survive up to 6 years. Branding is critical in determining business’ competitiveness and lifespan; therefore, it is crucial to identify ways to improve the MSEs branding. This research seeks to investigate how content marketing (CM) values affects relevant consumer or brand-related outcomes, which consists of informative value, emotional value, and social value on brand equity of service MSEs consumers. A questionnaire was distributed to 120 Indonesian service MSEs users to gather data. To evaluate the hypothesized relationships within the proposed model, this study utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, known for its relevance in exploratory research and sophisticated model estimation. Results revealed that emotional value and social value of CM each has positive influence towards brand equity. However, informative value does not have any influence towards brand equity. Findings of this study enrich the understanding on what values of CM campaign of Indonesian MSEs affects users’ attitude toward their brand. This study provides references for Indonesian service MSEs on how to produce effective contents, particularly in social media, as a part of their branding strategy.